2022
DOI: 10.1088/2053-1591/ac4e3f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on mechanical and wear properties of GNP/Carbon fiber/epoxy hybrid composites

Abstract: In this research, carbon fiber and Graphene nanoplatelets (GNP) of different weight percentages of GNP (0, 0.1,0.3, and 0.5 wt.%) reinforced hybrid composites were fabricated via hand layup technique followed by compression molding. For wear analysis to understand the correlation between control parameters (wt.% of filler, normal load, velocity, and sliding distance) and response measurements (weight loss), the design of experiments and analysis of variance (ANOVA) is used. The control variables such as normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…After adding nano ller GNP-MWCNT hybrid for 3 wt.%, the exural properties were relatively low. Nanoparticle aggregation, improper wetting, and void content are the major causes of decreasing the exural strength and modulus of the composite for further increasing nano ller content [33]. The epoxy tends to absorb water and form weak H 2 bonds, resulting in swelling and plasticisation of the polymer chain [27].…”
Section: Evaluation Of Mechanical Properties On the Effect Of Water A...mentioning
confidence: 99%
“…After adding nano ller GNP-MWCNT hybrid for 3 wt.%, the exural properties were relatively low. Nanoparticle aggregation, improper wetting, and void content are the major causes of decreasing the exural strength and modulus of the composite for further increasing nano ller content [33]. The epoxy tends to absorb water and form weak H 2 bonds, resulting in swelling and plasticisation of the polymer chain [27].…”
Section: Evaluation Of Mechanical Properties On the Effect Of Water A...mentioning
confidence: 99%
“…The decreased friction coefficient is due to the lubricating effect of GNPs in the CF-GCF/epoxy composite. 22
Figure 4.Variation of coefficient of friction with time for CF and GCF epoxy composite at (75 N, 12 Hz, 60°C).
…”
Section: Resultsmentioning
confidence: 99%
“…The decreased friction coefficient is due to the lubricating effect of GNPs in the CF-GCF/epoxy composite. 22 Figure 5(a) shows the weight loss and Figure 5(b) shows the specific wear rate along with the standard deviation on the bar chart of GCF/epoxy and CF/epoxy polymer composites. From Figure 5, it is observed that the weight loss and specific wear rate of GCF/epoxy polymer composite is less as compared to CF/epoxy polymer composite.…”
Section: Impact Of Gnps On the Tribological Properties Of Cfrp Compos...mentioning
confidence: 99%
“…Many engineering applications needing minimal friction and wear require epoxy nanocomposite materials with outstanding tribological characteristics. One of the most promising ways to solve the epoxy matrix's significant dry wear problem is by adding a carbon nanofiller [9,10]. Epoxy nanocomposites are widely employed in various sliding circumstances, including structural components and automotive and marine vessels [11][12][13].…”
Section: Introductionmentioning
confidence: 99%